Review Article: Simon Grennan, Roger Sabin, and Julian Waite, Marie Duval (Oxford: Myriad Editions, 2018). Issue 2 (1st September 2019) - Kunzle, David
Abstract : With Marie Duval, virtual creator of the ineffable Ally Sloper (first appearance 1867) and mainstay of a new magazine named Judy founded that year, we find a new kind of cartoon character, a new kind of caricature and a new kind of journal aiming, unlike Punch, at a female and lower-class audience. The moment was propitious: after two decades of national prosperity during which the GNP almost doubled, the demand (a push from below) was felt for some cultural irreverence and novelty. Maybe the 1850s and 1860s were the first 'Age of Leisure' rather than the succeeding one, that of Duval, proposed by the authors here (7); the later age, of Duval, was that of increased and lower-class leisure, for sure. This caricaturist and artist is a quite recent discovery: before the late 1980s and 1990, she was virtually unknown. She was Europe's first female professional exponent of caricature (as distinct from a few sisters in conventional cartooning), and her initials and name took credit for the long-term development of an extraordinary artistic property, which quickly became a new sociological phenomenon: a dissolute trickster called Ally Sloper. He attained wild popularity in the 1870s and 1880s, and beyond. He was the first of many British comic characters to become a household name, and the first such comic character to be widely commercialised.